1997
DOI: 10.1002/(sici)1096-9071(199707)52:3<243::aid-jmv2>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Detection of archetype and rearranged variants of JC virus in multiple tissues from a pediatric PML patient

Abstract: JC virus (JCV) establishes persistent infections in its human host, and in some immunocompromised individuals, the virus causes the fatal brain disease progressive multifocal leukoencephalopathy (PML). Two forms of the virus, archetype and rearranged, have been isolated, with the latter being derived from the archetype form by deletion and duplication of sequences within the viral transcriptional control region (TCR). We have used the PCR technique to amplify JCV TCR sequences present within multiple tissues o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
36
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 42 publications
1
36
0
1
Order By: Relevance
“…Our model more resembles cases of PML occurring in immunosuppressed children in the context of primary JCV infection. In one such case, multiple JCV archetype RR variants were present in different tissues (17). Nevertheless, regardless of the route of infection, and of the timing of SHIV immunosuppression with regard to SV40 infection, the archetype SV40 RR appears to be the pathogenic type associated with CNS disease in immunosuppressed monkeys, including both those with PML and those with ME.…”
Section: Discussionmentioning
confidence: 92%
“…Our model more resembles cases of PML occurring in immunosuppressed children in the context of primary JCV infection. In one such case, multiple JCV archetype RR variants were present in different tissues (17). Nevertheless, regardless of the route of infection, and of the timing of SHIV immunosuppression with regard to SV40 infection, the archetype SV40 RR appears to be the pathogenic type associated with CNS disease in immunosuppressed monkeys, including both those with PML and those with ME.…”
Section: Discussionmentioning
confidence: 92%
“…While tandem repeat variants have been found in the central nervous system of patients with PML, in brain tumors, and in peripheral lymphocytes of both PML and non-PML patients, the archetype has rarely been found in diseased brains. These findings suggest that the presence of a specific strain might reflect viral adaptation to the particular host tissue (4,16,19,22).Because the Mad-1 strain has the capacity for lytic infection of oligodendrocytes, JCV has always been considered strictly neurotropic. However, recent studies have shown that certain strains of JCV can replicate in lymphoid cells and that the capability of the virus to replicate in host cells is highly dependent on the structure of the TCR (2, 14).…”
mentioning
confidence: 88%
“…While tandem repeat variants have been found in the central nervous system of patients with PML, in brain tumors, and in peripheral lymphocytes of both PML and non-PML patients, the archetype has rarely been found in diseased brains. These findings suggest that the presence of a specific strain might reflect viral adaptation to the particular host tissue (4,16,19,22).…”
mentioning
confidence: 99%
“…Although the etiologic role of JCV in PML is well documented, the pathogenesis and, in particular, the role of viral determinants is less clear. Virtually all JCV strains isolated from the brain or CSF of PML patients are characterized by highly variable genomic rearrangements of the non-coding control region (NCCR), which governs viral early and late genes in opposite directions of the circular polyomavirus DNA genome (1,4,31,39,41,43,49,54,59). In contrast, JCV detected in the urine of immunocompetent individuals show a consistent linear architecture called the archetype NCCR (at-NCCR).…”
mentioning
confidence: 99%